The efficacy and safety of levilimab in severely ill COVID-19 patients not requiring mechanical ventilation: results of a multicenter randomized double-blind placebo-controlled phase III CORONA clinical study - Lomakin, Nikita V.; Bakirov, Bulat A.; Protsenko, Denis N.; Mazurov, Vadim I.; Musaev, Gaziyavdibir H.; Moiseeva, Olga M.; Pasechnik, Elena S.; Popov, Vladimir V.; Smolyarchuk, Elena A.; Gordeev, Ivan G.; Gilyarov, Mikhail Yu; Fomina, Darya S.; et al. (Inflammation research, 2021)
Objective and design The aim of this double-blind, placebo-controlled, phase III CORONA clinical trial was to evaluate the efficacy and safety of IL-6 receptor inhibitor levilimab (LVL) in subjects with severe COVID-19. Subjects The study included 217 patients. The eligible were men and non-pregnant women aged 18 years or older, hospitalized for severe COVID-19 pneumonia. Treatment 206 subjects were randomized (1:1) to receive single subcutaneous administration of LVL 324 mg or placebo, both in combination with standard of care (SOC). 204 patients received allocated therapy. After the LVL/placebo administration in case of deterioration of symptoms, the investigator could perform a single open-label LVL 324 mg administration as the rescue therapy. Methods The primary efficacy endpoint was the proportion of patients with sustained clinical improvement on the 7-category ordinal scale on Day 14. All efficacy data obtained after rescue therapy administration were considered missing. For primary efficacy analysis, all subjects with missing data were considered non-responders. Results 63.1% and 42.7% of patients in the LVL and in the placebo groups, respectively, achieved sustained clinical improvement on Day 14 ( P = .0017). The frequency of adverse drug reactions was comparable between the groups. Conclusion In patients with radiologically confirmed SARS-CoV-2 pneumonia, requiring or not oxygen therapy (but not ventilation) with no signs of other active infection administration of LVL + SOC results in an increase of sustained clinical improvement rate. Trail registration The trial is registered at the US National Institutes of Health (ClinicalTrials.gov; NCT04397562).